Canada : 2006 Article IV Consultation-Staff Report; Staff Supplement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2006)
Canada's macroeconomic and policy performance has continued to outshine most other industrial countries, and its outlook remains favorable. The new government has pledged to maintain the strong social consensus in favor of fiscal surpluses, while aiming at enhancing incentives. The new budget should ensure that a prudent fiscal framework is maintained. The favorable domestic and external environment will boost the economy's long-term growth potential. While the financial system appears well placed to support growth, there is still room to furthering its efficiency and resilience.